Profiling of miRNAs and target genes related to cystogenesis in ADPKD mouse models. Issue 1 (December 2017) - Woo, Yu; Kim, Do; Koo, Nam; Kim, Yong-Min; Lee, Sunyoung; Ko, Je; Shin, Yubin; Kim, Bo; Mun, Hyowon; Choi, Seonju; Lee, Eun; Shin, Jeong-Oh; et al.
Abstract Autosomal polycystic kidney disease (ADPKD) is a common inherited renal disease characterized by the development of numerous fluid-filled cysts in both kidneys. We investigated miRNA-mediated regulatory systems and networks that play an important role during cystogenesis through integrative analysis of miRNA- and RNA-seq using two ADPKD mouse models (conditionalPkd1- orPkd2 -deficient mice), at three different time points (P1, P3, and P7). At each time point, we identified 13 differentially expressed miRNAs (DEmiRs) and their potential targets in agreement with cyst progression in both mouse models. These targets were involved in well-known signaling pathways linked to cystogenesis. More specifically, we found that the actin cytoskeleton pathway was highly enriched and connected with other well-known pathways of ADPKD. We verified that miR-182-5p regulates actin cytoskeleton rearrangement and promotes ADPKD cystogenesis by repressing its target genes—Wasf2, Dock1, andItga4 —in vitro andin vivo . Our data suggest that actin cytoskeleton may play an important role in renal cystogenesis, and miR-182-5p is a novel regulator of actin cytoskeleton and cyst progression. Furthermore, this study provides a systemic network of both key miRNAs and their targets associated with cyst growth in ADPKD.